2019
DOI: 10.1186/s12951-019-0505-z
|View full text |Cite
|
Sign up to set email alerts
|

High drug-loading gold nanoclusters for responsive glucose control in type 1 diabetes

Abstract: Background Diabetes is one of the biggest medical challenges worldwide. The key to efficiently treat type 1 diabetes is to accurately inject insulin according to the blood glucose levels. In this study, we aimed to develop an intelligent insulin-releasing gold nanocluster system that responds to environmental glucose concentrations. Results We employed gold nanoclusters (AuNCs) as a novel carrier nanomaterial by taking advantage of their high drug-loading capacity. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…More recently, it has been reported that a glucose-responsive delivery system based on Au NCs can be used for the responsive insulin release and glucose control of type 1 diabetes, indicating the potential of metal NCs in the targeted therapeutics of diabetes. [237,238] Metal NCs, such as Au 25 Sv 9 , can reduce microglia-mediated cytotoxicity to neuronal cells and show direct neuroprotection in vitro. [239] Our group and others have demonstrated that both ultrasmall Au and Ag NCs can be used as nano-antibiotics for drug-resistant bacteria, indicating their potential in targeted antimicrobial therapy.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…More recently, it has been reported that a glucose-responsive delivery system based on Au NCs can be used for the responsive insulin release and glucose control of type 1 diabetes, indicating the potential of metal NCs in the targeted therapeutics of diabetes. [237,238] Metal NCs, such as Au 25 Sv 9 , can reduce microglia-mediated cytotoxicity to neuronal cells and show direct neuroprotection in vitro. [239] Our group and others have demonstrated that both ultrasmall Au and Ag NCs can be used as nano-antibiotics for drug-resistant bacteria, indicating their potential in targeted antimicrobial therapy.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…In addition to enzymes, some small molecules which have specific affinity to glucose are commonly used for detection of glucose. Among them, PBA and its derivatives are commonly used as the recognition agents for glucose [ [35] , [36] , [37] , [38] ], taking the advantage that PBA and its derivatives are able to reversibly bind with the adjacent diols of glucose [ 39 , 40 ]. This property of PBA was widely incorporated into smart hydrogels for biosensing of glucose [ 35 , 36 , 41 ].…”
Section: Smart Materials For Sensing Of Glucosementioning
confidence: 99%
“…DM, especially type 2 diabetes, is one of the most prevalent chronic diseases all over the world and has become the third threat to public health, after cardiovascular diseases and cancers (Zhang et al., 2019). It has been reported that ED is a common and yet underestimated complication of DM (Shiferaw et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The two most common medical problems that may cause ED are atherosclerosis (hardening of the arteries) and diabetes mellitus (DM) (Najari & Kashanian, 2016). DM, especially type 2 diabetes, is one of the most prevalent chronic diseases all over the world and has become the third threat to public health, after cardiovascular diseases and cancers (Zhang et al, 2019). It has been reported that ED is a common and yet underestimated complication of DM (Shiferaw et al, 2020).…”
mentioning
confidence: 99%